2019
DOI: 10.1002/hsr2.142
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific analysis of renal cell carcinoma histology and survival in Japan: A population‐based study 2004 to 2016

Abstract: Background and aims In Western countries, sex differences in renal cell carcinoma (RCC) histology and survival have been previously described: compared with men, clear cell subtype is more common but overall prognosis is better among women. The goal of the present study was to examine sex differences in RCC histology and survival in Japan, using a large‐scale population‐based data set. Methods With the use of a population‐based cancer registry in Japan (2004‐2016), patients with primary RCC were followed for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In the case of Figure 6 , the fact that chromosome Y is the only one with a higher cis- rate in control network than in ccRC stages may imply that, for this chromosome and its genes, local co-expression is crucial to maintain a proper functionality. It is widely known that two thirds of all ccRC cases correspond to men (Aron et al, 2008 ; Woldrich et al, 2008 ; Qu et al, 2015 ; Zaitsu et al, 2020 ). Since Chr Y is directly linked to gender, one may argue that an imbalance in the cis-/trans- proportion may be implicated in gender-bias on clear cell renal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Figure 6 , the fact that chromosome Y is the only one with a higher cis- rate in control network than in ccRC stages may imply that, for this chromosome and its genes, local co-expression is crucial to maintain a proper functionality. It is widely known that two thirds of all ccRC cases correspond to men (Aron et al, 2008 ; Woldrich et al, 2008 ; Qu et al, 2015 ; Zaitsu et al, 2020 ). Since Chr Y is directly linked to gender, one may argue that an imbalance in the cis-/trans- proportion may be implicated in gender-bias on clear cell renal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with ccRCC cases, patients with pRCC were significantly less likely to be female (odds ratio (OR): 0.60; 95% confidence interval (CI): 0.43-0.83), while patients with chRCC were significantly more likely to be female (OR: 2.32; 95% CI: 1.44-3.74). Despite the lower number of RCCs in Asia, a recent Japanese retrospective study [14] on 5265 patients with RCC (72.6% male, 27.4% female) confirmed the different distribution of histological subtypes between men and women. While the prevalence of ccRCC/"others" subtypes was similar between genders, pRCC was more prevalent among men, as compared to women (4.6% vs. 2.8%; p = 0.004), and chRCC was less prevalent among men, as compared to women (1.6% vs. 4.8%; p < 0.001).…”
Section: Gender-related Histological Characteristics Of Kidney Tumorsmentioning
confidence: 99%
“…Not all studies present a higher cancer-specific survival and overall survival in women rather than in men. Specifically, Zaitsu et al [14] analyzed a cohort of 5265 patients with RCC and equally distributed grades and stages (high grade:~10%, p = 0.85; late stage:~26%, p = 0.40). In the survival analysis, the five-year OS rate was 72% for both males and females, without statistically significant differences between genders, even after stratifying by histological subtypes.…”
Section: Impact Of Gender On Prognosismentioning
confidence: 99%
“…This difference may be clinically important, as it might partially explain the more favorable outcomes of RCC among females (considering the less aggressive behavior of chromophobe RCC) [12,105,116]. A recent Japanese retrospective study confirmed these findings [127]. Similarly, the sex-stratified analysis by Bhindi et al, found that the percentages of both malignant histology as well as aggressive histology were consistently higher for males [115].…”
Section: Histologymentioning
confidence: 88%